2
$\begingroup$

I am asked to prove

$$\mathbf{\det(I+xy^T+uv^T)}=(1+\mathbf{y^Tx})(1+\mathbf{v^Tu)-(x^Tv)(y^Tu)}$$

By first proving that $\mathbf{\det(I+xy^T)}=1+\mathbf{y^Tx}$, where $\mathbf{x}$ and $\mathbf{y}$ are $n$ vector.


Assuming that $x\neq0$, we can find vectors $w_1, w_2, \cdots, w_{n-1}$ such that the matrix $Q$ defined by $$Q=[x,w_1,w_2,\cdots, w_{n-1}]$$ is nonsingular and $x=Qe_1$, where $e_1=(1,0,0,\cdots,0)^T$. If we define $$y^TQ=(z_1,z_2,\cdots,z_n),$$ then $$z_1=y^TQe_1=y^TQ(Q^{-1}x)=y^Tx,$$ and $$\det(I+xy^T)=\det(Q^{-1}(I+xy^T)Q)=\det(I+e_1y^TQ).$$

After here I am not quite sure how to close the argument and then go on to prove that $\mathbf{\det(I+xy^T+uv^T)}=(1+\mathbf{y^Tx})(1+\mathbf{v^Tu)-(x^Tv)(y^Tu)}$.

$\endgroup$
1
$\begingroup$

With the same idea as in the proof of the matrix determinant lemma, one finds after a 'short' computation $$ \pmatrix{I&0&0\\ y^T&1&0\\ v^T&0&1} \pmatrix{I+xy^T+uv^T&x&u\\ 0&1&0\\ 0&0&1} \pmatrix{I&0&0\\ -y^T&1&0\\ -v^T&0&1} =\pmatrix{I&x&u\\ 0&y^Tx+1&y^Tu\\ 0&v^Tx& v^Tu+1}. $$ Note that this proof does not rely on any non-singularity condition.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Hint: First off, for any (compatible) matrices $A$ and $B$, we have $\det(I+AB) = \det(I+BA)$. In your case, $A$, $B$ are just column vectors.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.